Peningkatan Kemampuan Aparatur Desa Dalam Tata Kelola Pelaporan Keuangan Desa - Junaid Gazalin; La Asiri; Mansur Mansur; Sry Mayunita; Kastan Kastan; Rahmat Wiranto; Jumadil Jumadil; Ranti Ranti; Hanafi Hanafi (Journal of Community Development, 2022)
This community service activity (PKM) aims to increase the understanding and ability of the Sandang Pangan Village apparatus, Sampolawa District, South Buton Regency, in village administration governance as regulated by Permendagri No. 14 of 2016 concerning Guidelines for Village Government Administration and Permendagri No. 20 of 2018 concerning financial management. village. To create regularity in village administration, it is necessary to provide assistance in the preparation of administrative reporting, especially good and correct village financial reporting management. The purpose of community service activities is assistance and guidance to government officials, using the Participatory Learning and Action (PLA) approach or Participatory Learning and Practice Process. PLA is a community empowerment method consisting of a learning process (training, brainstorming, and discussion). The results of this service activity are 1) Village officials have known and understood good and correct village financial reporting management, as evidenced by the results of the training in the form of a draft report document according to the guidelines from the Ministry of Home Affairs regulations. 2) Village administration and village financial reporting so far have not been in accordance with the rules for their preparation, disorganized and irregular that has been carried out by village officials, changed for the better with the creation of a report module that is structured according to village administration. For this reason, efforts to improve the ability of village officials require a scheduled training program so that their competence in preparing report governance will be even better in the future.